Growth Inhibitory Activity of Indian Terminalia spp. against the Zoonotic Bacterium Bacillus anthracis - Wright, Mitchell Henry; Courtney, Reece; Greene, Anthony Carlson; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Anthrax is a zoonotic disease caused by the soil bacterium Bacillus anthracis. It has an extremely high mortality rate if untreated. Terminalia spp. have a long association with the treatment of various ailments, including bacterial infections although they have not been tested for the ability to inhibit the growth of B. anthracis. Methods: Solvent extracts were prepared using Terminalia spp. known to inhibit microorgan- ism growth. The antibacterial potential of the extracts were investigated by disc diffusion assay to determine the growth inhibitory potential against an environmental strain of B. anthracis. Their MIC values were calculated to quantify and compare their relative efficacies. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: Extracts prepared from several Indian Terminalia spp. displayed potent antibacterial activity in the disc diffusion assay against B. anthracis. The methanolic T. chebula fruit extract was particularly effective at inhibiting microbial growth, with MIC values against B. anthracis of 166 µg/mL (<2 µg impregnated in the disc). The aqueous T. chebula extract, as well as T. catappa and T. arjuna methanolic extracts, were also good growth inhibitors with MIC’s generally <2500 µg/mL (<25 µg impregnated in the disc). All other plant extracts were either inactive or of only low inhibitory activity. None of the extracts were deemed toxic, with all recorded LC50 values substantially>1000 µg/mL. Conclusion: The potent growth inhibitory activity of the methanolic T. che- bula fruit extract against B. anthracis indicates its potential in the treatment and prevention of anthrax. Furthermore, due to its low toxicity,its use may extend to all forms of the disease (cutaneous, inhalation or gastrointestinal) and may extend to live stock as well as humans.
Keywords: Terminalia; Antibacterial activity; Terminalia chebula; Terminalia catappa; Terminalia arjuna; Anthrax; Traditional medicine